PEREMPUAN DALAM PENGELOLAAN SURAT KABAR DI SULAWESI TENGAH (Studi Posisi dan Peran Perempuan dalam Media Cetak) - Lampe, Ilyas (Academica, 2010)
359PEREMPUAN DALAM PENGELOLAAN SURAT KABARDI SULAWESI TENGAH(Studi Posisi dan Peran Perempuan dalam Media Cetak)Oleh : Ilyas1ABSTRACTWomenâs presentation in mass media, especially in printed media,is always in a negative sense. They are living as a decoration and sexualobject. We can say that this is hapening due to the patriarchal culturewhich make people who work in a media is dominated by male and theprocess of media is also dominated by them.The main reason of this research is to answer the question, 1. Howmany women is involved in the process of printed media in CentralSulawesi 2. Can women who involved in printed media influence the policyof media related to gender issue 3. Into which many levels mass mediamanagement gives a tolerance to gender issue.The reslut of this study, which is using gender analysis, is takenfrom three biggest printed media in Sulawesi. It shows that the percentageof women journalist is only 15,27 %. Furthermore, we can see how weakwomen journalist is to influence the news management in these printedmedia due to the portion of the job which most of the women in a printedmedia is positioned in a light section, e.g. Entertainment, Technology andScience, Education and Culture. On top of that, the power of capitalismshapes printed media to have no sensitivity in gender issue. Themanagement gives more concern to gain the profit, or even if they doconcern, they only use gender issue as a tool to gain bigger profit.Keyword : Women Role, Printed Media Management